Effect of polyethylene glycol versus lactulose on abdominal pain in children occult constipation: a randomized controlled study - Hakimzadeh, Mehran (2020)
Introduction and aim: Functional abdominal pain (FAP) is one of the major astrointestinal complaints in childhood. Studies have reported occult constipation (OC) as one of the leading causes of abdominal pain. Recent researches have proposed laxatives as potent therapeutic targets for abdominal pain in patients with OC. However, no study has compared effect of poly ethylene glycol (PEG) and lactulose on occult constipation. Materials and methods: 51 patients aged 4 to 18 years with abdominal pain who had OC (defined as fecal impaction in abdominal X ray) were studied. Demographic and clinical data including age, sex, body weight, height, abdominal pain duration, abdominal pain rate and fecal odor were registered. They were randomly assigned to receive PEG (1gr/kg) or Lactulose (1cc/kg) for at least two weeks. All patients were reevaluated by pain measurement scale after at least two weeks of treatment. Results: It is indicated that the efficacy of PEG for reducing abdominal pain in OC was 48% while it was 37% for Lactulose. This study indicated that this efficacy is not affected significantly by sex and fecal odor, however this efficacy is influenced by age, body weight, abdominal pain duration and abdominal pain rate for both PEG and Lactulose. Conclusion: It could be concluded that PEG is a more efficient drug for treating abdominal pain in occult constipation than Lactulose and its optimum effect can be achieved in elder patients with more severe abdominal pain. Introduction and aim: Functional abdominal pain (FAP) is one of the major gastrointestinal complaints in childhood. Studieshave reported occult constipation (OC) as one of the leading causes of abdominal pain. Recent researches have proposedlaxatives as potent therapeutic targets for abdominal pain in patients with OC. However, no study has compared effect ofpoly ethylene glycol (PEG) and lactulose on occult constipation. Materials and methods: 51 patients aged 4 to 18 years withabdominal pain who had OC (defined as fecal impaction in abdominal X ray) were studied. Demographic and clinical dataincluding age, sex, body weight, height, abdominal pain duration, abdominal pain rate and fecal odor were registered. Theywere randomly assigned to receive PEG (1gr/kg) or Lactulose (1cc/kg) for at least two weeks. All patients were reevaluated by painmeasurement scale after at least two weeks of treatment. Results: It is indicated that the efficacy of PEG for reducing abdominalpain in OC was 48% while it was 37% for Lactulose. This study indicated that this efficacy is not affected significantly by sex andfecal odor, however this efficacy is influenced by age, body weight, abdominal pain duration and abdominal pain rate for bothPEG and Lactulose. Conclusion: It could be concluded that PEG is a more efficient drug for treating abdominal pain in occultconstipation than Lactulose and its optimum effect can be achieved in elder patients with more severe abdominal pain.